Analisis Etika Publik Dalam Mencapai Good Governance di Badan Kepegawaian Daerah (BKD) Provinsi Sumatera Barat - Syahrunisya Salsabila Putri; Laurra Acsa Liani; Diva Meirista; Bisis Manita; Yulia Hanoselina; Rahmadhona Fitri Helmi (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This study examines the implementation of public service ethics at the Regional Civil Service Agency (BKD) of West Sumatra Province as an effort to achieve good governance. Good public service ethics contribute to enhancing service quality and transparency in personnel administration. The findings indicate that BKD has implemented various standard operating procedures (SOPs) and communication strategies, including the use of social media, to improve information access and responsiveness to complaints. Despite challenges such as maladministration and insufficient socialization, BKD is committed to improving services and building trust among the public and civil servants.